2021
DOI: 10.1177/0192513x211042847
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors of Male Survivors of Intimate Partner Violence in Kenya

Abstract: Very few studies examine the help-seeking behaviors of male survivors of intimate partner violence (IPV) in Kenya or sub-Saharan Africa more generally. Using nationally representative cross-sectional data from 1,458 male survivors and multinomial logit models, we examined what influences men’s decision to seek help after experiencing IPV. Results show the majority of male survivors did not seek help. Those who did so turned to informal rather than formal sources. The severity of physical violence was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A study was conducted to examine the prevalence of past-year IPV experience and perpetration among women and men living in an informal settlement in Kenya and factors associated with IPV among 273 women and 429 men (Ringwald et al, 2022). This study’s results revealed that women and men experienced similar levels of IPV, but a significantly higher proportion of men reported physical and sexual IPV perpetration, another study in Kenya reported that 6.8, 3.6, and 20.1% of Kenyan men had experienced physical, sexual, and emotional violence, respectively (Tenkorang et al, 2021). Furthermore, another study conducted among individuals in a hospital emergency department in Hong Kong revealed a higher representation of family violence among Chinese male victims, as opposed to females, in the 20 to 49 years old category, and more male victims in critical conditions than female IPV victims (Chan et al, 2013; Tsang et al, 2021).…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…A study was conducted to examine the prevalence of past-year IPV experience and perpetration among women and men living in an informal settlement in Kenya and factors associated with IPV among 273 women and 429 men (Ringwald et al, 2022). This study’s results revealed that women and men experienced similar levels of IPV, but a significantly higher proportion of men reported physical and sexual IPV perpetration, another study in Kenya reported that 6.8, 3.6, and 20.1% of Kenyan men had experienced physical, sexual, and emotional violence, respectively (Tenkorang et al, 2021). Furthermore, another study conducted among individuals in a hospital emergency department in Hong Kong revealed a higher representation of family violence among Chinese male victims, as opposed to females, in the 20 to 49 years old category, and more male victims in critical conditions than female IPV victims (Chan et al, 2013; Tsang et al, 2021).…”
mentioning
confidence: 63%
“…Other studies mentioned that some participants identified as being in a current relationship during the study (Bates, 2020; Hogan et al, 2021). Some of the included studies stated the participants’ employment status, education level, and occupations (Dim & Lysova, 2022; Donne et al, 2018; Freeland et al, 2018; Goldberg-Looney et al, 2016; Gonçalves et al, 2021; Gueta & Shlichove, 2022; Machado et al, 2016; Simon & Wallace, 2018; Tenkorang et al, 2021; Tsang et al, 2021; Tsui et al, 2014; Walker et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The argument here is that gender socialization may cause men to minimize or trivialize their experiences of IPV [ 62 , 70 ], but may also hinder them from disclosing their IPV experiences and from taking the decision to seek help [ 48 , 64 , 71 , 72 ]. Several studies carried out elsewhere also indicate that men avoid seeking help after victimization for fear of being ridiculed, because they feel ashamed, and ultimately for fear of being considered the initiator of violence rather than the victim [ 48 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%